Which Predictor is the Most Important? Examining the Unique Contribution of Violence Perception Dimension against the Prevalence of Digital Violence - Dini Rakhmawati; Heri Saptadi Ismanto; Jovita Julienjatiningsih; Tri Suyati (Kuras Institute, 2026)
This study analyzed the influence of different dimensions of gender-based violence perceptions on the prevalence of digital violence (DV) among university students. The research background rests on the growing threat of online violence, which may be shaped by individual awareness levels. The research instrument specifically accommodated four forms of online gender-based violence: digital sexual harassment, violence based on physical appearance, violence based on gender roles, and anti-feminist violence. The study employs a cross-sectional design and involves 414 students who actively use social media as respondents. Multiple regression analysis (F-test) shows that the four perception dimensions—perceptions of sexual harassment, gender-based violence, physical appearance violence, and anti-feminist violence—simultaneously exert a significant effect on digital violence (Sig. = 0.001). These results confirm the validity of the predictive model. However, partial testing (t-test) reveals that only perceptions of sexual harassment significantly and positively influence digital violence (B = +0.304; Sig. = 0.002). The positive coefficient reflects a reporting bias: respondents with higher sensitivity to sexual harassment tend to define and report a broader range of online incidents as violence. Meanwhile, perceptions of gender-based violence, physical appearance violence, and anti-feminist violence do not provide unique predictive contributions. The study concludes that, in the context of digital violence, sexual harassment awareness is the most dominant factor. It recommends that online violence prevention programs and policies focus specifically on strengthening understanding and coping strategies related to digital sexual harassment.